BIEGUNY DUCHA NARODU POLSKIEGO. WOKÓŁ NORWIDOWSKIEJ LEKCJI IV WYKŁADÓW O SŁOWACKIM - Rzepczyński, Sławomir (Colloquia Litteraria, 2019)
Extremities of the Spirit of the Polish Nation. On Norwid’s Lekcja IV from his lectures on Słowacki The article attempts to reconstruct Norwid’s philosophy of history, focusing on Lekcja IV from his lectures O Juliuszu Słowackim. According to the poet every civilization (culture) has a particular mission to fulfill in history. The beginning of this mission is always a continuation of the work initiated by Christ himself. Christ turned the existential dimension of being from the individual to the collective and as such designed the scope for activity of nations as subjects of history. Nations are to liberate themselves from ethnic particularities and bring about the moral transformation of the mankind; this should happen through the recognition of the signum of their own historical time and its relations to Christ’s tradition as well as undertaking of the postulate to perfect their contemporary times. To advance his goals Norwid performs a particular, deliberate overinterpretation of works by Zygmunt Krasiński and Juliusz Słowacki. From Krasiński’s Legenda he takes the appointment of the initial ‘Roman’ (after-Christ, catholic) extremity of the Polish civilization; from Słowacki’s Anhelli the declining ‘Siberian’ extremity, which is transformed by love as a result of suffering. This concept by Norwid clashes with Romantic, mystic-messianic ideas, which bound the Redemption of the man with otherworldly heroism of the spirit denying mortal life; it, furthermore, brings out a particular criticism of all ideas linking existence with unchanging being in mortal life.